Chronic Psychosocial Stress Impairs Bone Homeostasis: A Study in the Social Isolation Reared Rat - Schiavone, Stefania; Morgese, Maria G.; Mhillaj, Emanuela; Bove, Maria; De Giorgi, Angelo; Cantatore, Francesco P.; Camerino, Claudia; Tucci, Paolo; Maffulli, Nicola; Cuomo, Vincenzo; Trabace, Luigia (Frontiers in Pharmacology, 2016)
Chronic psychosocial stress is a key player in the onset and aggravation of mental diseases, including psychosis. Although a strong association between this psychiatric condition and other medical co-morbidities has been recently demonstrated, few data on the link between psychosis and bone homeostasis are actually available. The aim of this study was to investigate whether chronic psychosocial stress induced by 4 or 7 weeks of social isolation in drug-naïve male Wistar rats could alter bone homeostasis in terms of bone thickness, mineral density and content, as well as markers of bone formation and resorption (sclerostin, cathepsin K and CTX-I). We found that bone mineral density was increased in rats exposed to 7 weeks of social isolation, while no differences were detected in bone mineral content and area. Moreover, 7 weeks of social isolation lead to increase of femur thickness with respect to controls, suggesting the development of a hyperostosis condition. Isolated rats showed no changes in sclerostin levels, a marker of bone formation, compared to grouped animals. Conversely, bone resorption markers were significantly altered after 7 weeks of social isolation in terms of decrease in cathepsin K and increase of CTX-I. No alterations were found after 4 weeks of isolation rearing. Our observations suggest that chronic psychosocial stress might affect bone homeostasis, more likely independently from drug treatment. Thus the social isolation model might help to identify possible new therapeutic targets to treat the burden of chronic psychosocial stress and to attempt alternative therapy choices.